Efficacy and Durability of Intratympanic Gentamicin Treatment for Meniere's Disease - Guan, Yafeng; Chari, Divya A.; Liu, Yu-Hsi; Rauch, Steven D. (Frontiers in Neurology, 2021)
Objective: To study the success of intratympanic gentamicin (ITG) treatment in reducing vertigo attacks in Meniere’s disease (MD) and the value of the Halmagyi head thrust test (HTT) in predicting treatment durability. Study Design: Retrospective cohort study. Setting: Tertiary care vestibular clinic. Patients: Unilateral MD patients treated with ITG from 2006-2019 with ≥6 months follow-up. Main Outcome Measures: Demographics, audiometric data, subjective symptomatology, and HTT results were collected. Treatment success was defined as sufficient symptom relief. Treatment failure indicated vertigo control of less than 6 months duration. Treatment relapse indicated vertigo recurrence after 6 months. Results: Of 255 patients, treatment success, failure, and relapse occurred in 105 (41.3%), 29 (11.4%), and 121 (47.1%) patients, respectively. 48 (18.5%) patients who failed to respond or relapsed underwent labyrinthectomy. Mean follow-up time was 3.7 yrs (range 0.5-12.8). After ITG treatment, 25% patients reported worse hearing; mean pure tone average (PTA) increased by 18.6±11.3 dB and mean word recognition score (WRS) decreased by 33±21%. Of the 148 patients with negative pre-treatment HHT, 103 (69.6%) converted to positive after ITG treatment. Mean time to relapse in the converted and non-converted HTT cohorts was significantly different (49.7 vs. 27.0 months, p=0.009) even after adjusting for gender, age, laterality, duration of symptoms, and number of ITG treatments. There were no significant differences between the two groups in hearing outcomes or subjective symptoms (e.g. lingering disequilibrium). Conclusions: ITG treatment effectively reduces the number of vertigo attacks in MD. HTT is valuable in predicting durability of treatment benefit.